Principles Adopted by Abu Ubaida in his book (metaphor of the Koran) (Journal of the College of Education for Women, 2019)
Praise be to God, prayer and peace be upon the Messenger of Allah and after: The science of interpretation is related to the book of God Almighty; it is considered one of the most honorable sciences. It started with a long time ago. In the early days of Islam, the area of ​​the Islamic state expanded. The people entered the religion of Allah in groups. In the language, and people do not know more than the meanings of the Koran was the need to write in this scie234nce is strong, and perhaps the first of the thousand in the (meanings of the Koran) Abu Ubaida in his book (metaphor of the Koran), Abu Ubaida was affected by his specialization in Arabic science, Prominent on his book.The second section was based on the principles adopted by Abu Obeida in his interpretation, in which he explained the Qur'an's interpretation of the Qur'an, the interpretation of the Qur'aan in the Sunnah, and the interpretation of the Qur'an with the words of the Companions and the Companions.